Crystal structure and spectroscopic properties of polymeric adducts of the tetra-μ-haloaspirinate-dicopper(II) - Rustoy, Eduardo Miguel (2012)
Eight new copper(II) complexes with halo-aspirinate anions have been synthesized: [Cu 2(Fasp) 4(MeCN) 2]·2MeCN (1), [Cu 2(Clasp) 4(MeCN) 2]·2MeCN (2), [Cu 2(Brasp) 4 (MeCN) 2]·2MeCN (3), {[Cu 2(Fasp) 4(Pyrz)]·2MeCN} n (4), {[Cu 2(Clasp) 4(Pyrz)]·2MeCN} n (5), [Cu 2(Brasp) 4(Pyrz)] n (6), [Cu 2(Clasp) 4(4,4'-Bipy)] n (7), and [Cu 2(Brasp) 4(4,4'-Bipy)] n (8) (Fasp: fluor-aspirinate; Clasp: chloro-aspirinate; Brasp: bromo-aspirinate; MeCN: acetonitrile; Pyrz: pyrazine; 4,4'-Bipy: 4,4'-bipyridine). The crystal structure of two 2 and 4 have been determined by X-ray diffraction methods. All compounds have been studied employing elemental analysis, IR, and UV-Visible spectroscopic techniques. The results have been compared with previous data reported for complexes with similar structures. © 2012 Taylor & Francis.